Calibration of Digital Camera with the help of Processing Programs of Computer Images - E. N. Savkova (Наука и техника)
While investigating brightness characteristics of computer images obtained with the help of a digital camera in the conditions of low light and long time exposures (starting from 1/8... 1/4 sec) it is necessary to take into account and, at the possible opportunity, to exclude defects (graininess effect, spot dissemination of raised brightness). These defects are attributed to leakage currents and imperfection of DDD-structure of the chamber as they cause casual errors in the results of measurements. Removal of defects is reached by the calibration of digital cameras which is made with the help of special software products.The paper considers the opportunities of some existing noise analyzing programs, methods of digital image processing with the help of such devices as Adobe Photoshop 6 and Thumber. Application of these devices improves an accuracy of mathematical processing of measurements.